THE EFFECT OF ADVERTISING AND WORD OF MOUTH ON ONLINE PURCHASING BEHAVIOR OF STUDENTS OF THE FACULTY OF ECONOMICS, UNIVERSITAS SERAMBI MEKKAH - Susanti; Wahyuli; Saiful Amri; Samsul Ikhbar (Lembaga Riset dan Inovasi Kreyat Center, 2023)
The purpose of this study was to study the Effect of Advertising and Word of Mouth on Online Purchasing Behavior at the Faculty of Economics, Serambi University, Mecca, Jln Tgk Imum Lueng Bata, Lueng Bata, Batoh, Banda Aceh. The population in this study were students of the Faculty of Management Economics of the University of Serambi Mecca. Primary data collection is done through a questionnaire distributed to students. The analytical method used is hypothesis testing using multiple linear regression. Simultaneous hypothesis testing results and word-of-mouth promotion of online purchasing behavior at the Faculty of Economics, Serambi University, Mecca. While testing individual hypotheses are adverts against online purchasing behavior, and also word of mouth against online purchasing behavior in students of the Faculty of Economics Management of Serambi University.